Control of hypertension in children after renal transplantation - Seeman, Tomás; Simková, Eva; Kreisinger, Jirí; Vondrák, Karel; Dusek, Jirí; Gilík, Jirí; Feber, Janusz; Dvorák, Pavel; Janda, Jan (Pediatric transplantation, 2006)
The aim of this cross-sectional single-center study was to investigate the efficacy of hypertension control in children who underwent transplantation using ambulatory blood pressure (BP) monitoring, and to determine the risk factors associated with poor control of hypertension. Thirty-six children fulfilled the inclusion criteria. The mean age was 13.9+/-4.4 yr; the mean time after renal transplantation was 2.7+/-2.4 yr (0.5-10.1). Hypertension was defined as a mean ambulatory BP > or =95th centile for healthy children and/or requiring antihypertensive drugs. Hypertension was regarded as controlled if the mean ambulatory BP was <95th centile in children already on antihypertensive drugs, or uncontrolled if the mean ambulatory BP was > or =95th centile in treated children. Hypertension was present in 89% of children. Seventeen children (47%) had controlled hypertension, and 14 (39%) had uncontrolled hypertension. One child (3%) had untreated hypertension, and only four children (11%) showed normal BP without antihypertensive drugs. The efficacy of hypertensive control was 55% (17 of 31 children on antihypertensive drugs had a BP<95th centile), i.e. 45% of treated children still had hypertension. Children with uncontrolled hypertension had significantly higher cyclosporine doses (6.1 vs. 4.3 mg/kg/day, p=0.01) and tacrolimus levels (9.2 vs. 6.1 microg/L, p<0.05), and there was a tendency toward use of lower number of antihypertensive drugs (2.0 vs. 1.5 drugs/patient, p=0.06) and lower use of angiotensin-converting enzyme (ACE) inhibitors (7 vs. 35%, p=0.09) and diuretics (29 vs. 59%, p=0.14) than in children with controlled hypertension. In conclusion, nearly 90% of our children after renal transplantation are hypertensive and the control of hypertension is unsatisfactorily low. The control of hypertension could be improved by increasing the number of prescribed antihypertensive drugs, especially ACE inhibitors, and diuretics, or by using higher doses of currently used antihypertensives.
Keywords: Humans; echokardiografie; dítě; Hypertension; Echocardiography; Child; Female; dospělí; výsledek terapie; Antihypertensive Agents; lidé; Blood Pressure Monitoring, Ambulatory; ambulantní monitorování krevního tlaku; časové faktory; předškolní dítě; Adult; transplantace ledvin; ženské pohlaví; krevní tlak; Male; hypertenze; Adolescent; Treatment Outcome; Kidney Transplantation; antihypertenziva; mužské pohlaví; Child, Preschool; Blood Pressure; Time Factors; mladiství